Advances in endoscopic resection techniques of small gastric tumors originating from the muscularis propria - Khan, Suliman; Cui, Xiaona; Nasir, Safyan; Rafiq, Shoaib Mohammad; Qin, Bo; Bai, Qian (Frontiers in Oncology, 2022)
Gastrointestinal stromal tumors are common gastrointestinal tumors typically originating from the muscularis propria layer of the stomach. Small gastric stromal tumors are usually detected incidentally during routine endoscopic examination. Although they may have malignant potentially, controversies remain regarding the need for endoscopic resection of small gastric stromal tumors originating from the muscularis propria. According to the guidelines of the European Society of Medical Oncology, all gastrointestinal stromal tumors >2 cm in size should be resected with endoscopic surveillance recommended for tumors <2 cm. Endoscopic resection including endoscopic mucosal dissection (EMD), endoscopic submucosal dissection (ESD), submucosal tunneling endoscopic resection and snare assisted endoscopic resection. However, EMD and ESD procedures may be accompanied with serious complications including perforation, bleeding, and abdominal infection. Snare-assisted endoscopic resection is an alternative approach and has the advantages of a shorter procedure time and a low rate of perforation or bleeding. This study summarizes the safety and feasibility of a novel snare-assisted endoscopic resection technique and highlights the pros and cons of the different endoscopic approaches currently used for subepithelia small gastric tumors.